Coenzyme Q10 supplementation effects on lipid ratios in women with type 2 diabetes mellitus: A randomized, double-blind clinical trial study - Zarei, Parvin; Rezvanfar, Mohammad Reza; Khosrowbeygi, Ali (Bangladesh Journal of Medical Science, 2019)
Objective: This study had been designed to evaluate the effects of Coenzyme Q10 (CoQ10) supplementation on the lipid ratios in women with type 2 diabetes mellitus (T2DM). Materials and Methods: Sixty-eight women with T2DM were enrolled and randomly divided into two groups. While one group received 100 mg/day of CoQ10 supplement for 12 weeks (n=34) the other was given placebo for the same time duration (n=34). Lipid profile including triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were evaluated at the beginning and at the end of the intervention and lipid ratios were calculated. Results and Discussion: After the intervention, values of non-HDL-C (p=0.001), TG/HDL-C (p=0.03) and LDL-C/HDL-C (p=0.001) were significantly decreased in CoQ10 group. Values of HDL ratio (p=0.002) were increased significantly in CoQ10 group. Conclusion: This study showed that daily supplementation with 100 mg of CoQ10 in women with T2DM could improve some atherogenic lipid ratios that might be useful in preventing cardiovascular diseases in them. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.152-158